Anti-Theodicy and Atheism in Albert Camus - Ramírez Medina, Ángel (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The existence of evil, in particular, the evil suffered by innocent victims, like children, has been one of the arguments given by Camus against the existence of a God considered to have the attributes of Goodness and Omnipotence. Set in a creationist consideration of the world, the presence of evil gives us the opportunity to subject the Creator-God to a judgment that justifies his work before the existence of evil. This is what we mean by «theodicy», a neologism created by Leibniz in 1710 to refer to the defense of God before the problem of evil.